Recent advances in the diagnosis and treatment of peritoneal dialysis-associated peritonitis - Hou Shi-hui; Yang Jie; He Ya-ni; Chen Ke-hong (Linchuang shenzangbing zazhi)
Peritonitis associated with peritoneal dialysis is a common complication of peritoneal dialysis with a high level of morbidity and mortality. Early diagnosis and timely and accurate anti-infective regimen are vital for boosting the success rate of peritonitis treatment. Based upon the diagnosis， treatment and prevention of peritonitis， this review summarized the timing of peritonitis treatment， the choice of antibiotics， the mode of antibiotics administration and the removal of peritoneal dialysis tubes. Some novel techniques， such as polymerase chain reaction （PCR） and matrix-assisted laser desorption ionization time of flight mass spectrometry， were introduced for rapid detection of pathogenic microorganisms. The causes of refractory peritonitis and the pharmacokinetics and pharmacodynamics of antibiotics during peritoneal dialysis were also discussed. Monitoring the concentrations of different antibiotics may enable more accurate anti-infections. The review was intended to provide directions and suggestions for further researches on peritonitis for lowering the incidence of peritonitis and improving the success rate of treatment.